Analysis the performance of unsignalized intersection based on gap acceptance studies - Syafiqah, Mohamed Salleh (2012)
The mam purposed of this study was to analysis the performance of unsignalized intersection based on gap acceptance study. Unsignalized intersection plays an important role in determining the capacity of road network especially in urban and suburban areas. A poorly operating unsignalized intersection may affect a signalized network or operation of an Intelligent Transport System. The T-junction for this study was controls by stop rule or in other names is two-way stop controlled intersection (TWSC). For a TWSC intersection, the stop controlled approaches are referred to as the minor road approaches. The most important parameters affecting the capacity and performance of unsignalized intersection are the critical gap. Basically, critical gap are establish by Highway Capacity Manual. Therefore, the critical gap is difference between each intersection based on the geometry of the road, numbers of lane, and surrounding area located near the intersection. Critical gap can not be determined directly from field but data of accepted and rejected gaps can be collected and analysed. Data of gaps were collected using video camera and several equipments. Raff s method was used in determination of critical gap. In this study, critical gap was divided into three sections which is RT from major road, RT and LT from minor road. The values of critical gap vary from 2 seconds to 7 seconds. Critical gap value that was established by HCM and from field observation was input in Sidra software to analyze the performance of the intersection. Based on analysis of output produced from Sidra software, there is found output were obtained from field observation is more closed with the actual field condition. Therefore, the performance at a TWSC intersection can be determined from this analysis in terms of queue and level of services. This study can be continued in the future in order to improve the value of input parameters and also develop the analysis procedure for four leg intersection and roundabout not only for urban and suburban areas, but also for rural area.